COMPARISON OF RHEOLOGICAL AND MECHANICAL PROPERTIES OF MODIFIED POLYPROPYLENE – SHORT GLASS FIBER COMPOSITES - Shahid, S.; Ali, A.; Khan, M. N.; Khan, M. B. (The Nucleus, 2020)
Short glass fiber (SGF) reinforced composite materials were principally fabricated using polypropylene (PP) as thermoplastic matrix. Short glass fiber and polypropylene frequently suffer from lack of adequate fiber-matrix adhesion. This problem was addressed by grafting polypropylene (PP) with maleic anhydride (MA) in the presence of benzyl peroxide (BPO) as an initiator. The results revealed that by increasing fiber contents from 5 to 40 %, tensile strength increases while elongation at break decreases. Rheological behavior was found to be pseudoplastic, whereas viscosity increases by increasing SGF contents. A decrease in die swell was observed with increase in SGF contents.